Decreased mortality among patients with catheter-related bloodstream infections at Catalan hospitals (2010–2019). (August 2022) - Badia-Cebada, L.; Peñafiel, J.; López-Contreras, J.; Pomar, V.; Martínez, J.A.; Santana, G.; Cuquet, J.; Montero, M.M.; Hidalgo-López, C.; Andrés, M.; Gimenez, M.; Quesada, M.D.; et al.
Summary: Background: The incidence of catheter-related bloodstream infections (CRBSIs) has fallen over the last decade, especially in intensive care units (ICUs). Aim: To assess the existence of concomitant trends in outcomes and to analyse the current risk factors for mortality. Methods: A multicentre retrospective cohort study was conducted at 24 Catalan hospitals participating in the Surveillance of healthcare-associated infections in Catalonia (VINCat). All hospital-acquired CRBSI episodes diagnosed from January 2010 to December 2019 were included. A common protocol including epidemiological, clinical, and microbiological data was prospectively completed. Mortality at 30 days after bacteraemia onset was analysed using the Cox regression model. Findings: Over the study period, 4795 episodes of CRBSI were diagnosed. Among them, 75% were acquired in conventional wards and central venous catheters were the most frequently involved (61%). The 30-day mortality rate was 13.8%, presenting a significant downward trend over the study period: from 17.9% in 2010 to 10.6% in 2019 (hazard ratio (HR): 0.95; 95% confidence interval (CI): 0.92–0.98). The multivariate analysis identified age (HR: 1.03; 95% CI: 1.02–1.04), femoral catheter (1.78; 1.33–2.38), medical ward acquisition (2.07; 1.62–2.65), ICU acquisition (3.45; 2.7–4.41), S. aureus (1.59; 1.27–1.99) and Candida sp. (2.19; 1.64–2.94) as risk factors for mortality, whereas the mortality rate associated with episodes originating in peripheral catheters was significantly lower (0.69; 0.54–0.88). Conclusion: Mortality associated with CRBSI has fallen in recent years but remains high. Intervention programmes should focus especially on ICUs and medical wards, where incidence and mortality rates are highest.